The handbook of global climate and environment policy (Oxford, 2013)
"The Handbook of Global Climate and Environment Policy presents an authoritative and comprehensive overview of global policy on climate and the environment. It combines the strengths of an interdisciplinary team of experts from around the world to explore current debates and the latest thinking in the search for global environmental solutions."